2001
DOI: 10.1177/001440290106700302
|View full text |Cite
|
Sign up to set email alerts
|

Arithmetic Performance of Students: Implications for Standards and Programming

Abstract: This article presents a description of the arithmetic performance of students with mild disabilities and general education students and discusses these data in terms of student achievement and its implications for standards and programming. The data were obtained across grade levels 3–8 on 937 general education students and 197 students with mild disabilities. The data are discussed in terms of selected mathematics standards (e.g., Principles and Standards of School Mathematics NCTM, 2000) and Public Law 105–1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
58
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 5 publications
2
58
0
3
Order By: Relevance
“…Assessments conducted at state, national, and international levels over the past 30 years have indicated that U.S. students are "notably deficient" in their ability to solve mathematical problems (National Research Council [NRC], 2001, p. 4). Students with learning disabilities manifest even more severe problems (Cawley, Parmar, Foley, Salmon, & Roy, 2001). Improving mathematics performance of all students, including those with learning disabilities or difficulties, is one of the nation's priorities (National Education Goals Panel, 1997).…”
mentioning
confidence: 99%
“…Assessments conducted at state, national, and international levels over the past 30 years have indicated that U.S. students are "notably deficient" in their ability to solve mathematical problems (National Research Council [NRC], 2001, p. 4). Students with learning disabilities manifest even more severe problems (Cawley, Parmar, Foley, Salmon, & Roy, 2001). Improving mathematics performance of all students, including those with learning disabilities or difficulties, is one of the nation's priorities (National Education Goals Panel, 1997).…”
mentioning
confidence: 99%
“…School-based problems are typically embedded in text-laden descriptions, which some students with low math and reading skills cannot understand and do not find motivating (Cawley, Parmar, Foley, Salmon, & Roy, 2001;Ellis, 1998;Miller & Mercer, 1997;Mtetwa & Garofalo, 1989). The inability to comprehend text severely limits these students' ability to construct the mental models, or pictures, of problem contexts that are necessary for solving authentic problems (Norman, 1983;Shepard & Cooper, 1982).…”
mentioning
confidence: 99%
“…It is important to recognize also that many students may simply have difficulty recalling directions or information presented orally (e.g., writing numbers from dictation; Bley & Thornton, 1995). Another challenge students frequently encounter is an underdeveloped mathematics language base (Cawley, Parmar, Foley, Salmon, & Roy, 2001). In particular, students may struggle to understand significant mathematical terms, especially terminology with multiple meanings or applications (e.g., sum, times, difference; Bley & 216 C. N. Thomas et al Thornton, 1995).…”
Section: Receptive Language Challengesmentioning
confidence: 99%
“…Along with other receptive language skills, solving word problems depends heavily on good comprehension skills. Poor comprehension skills may result in difficulty managing extraneous information and an overreliance on cue words (e.g., all together means addition), resulting in incorrect interpretation or understanding of the problem (Cawley et al, 2001; N. C. Jordan et al, 2003), particularly problems with multiple steps (Bley & Thornton, 1995), as well as failing to apply strategies designed to aid in comprehension and understanding (e.g., asking oneself, ''Have I seen the problem before?'') and verifying answers (i.e., settling for the first solution derived; Bryant et al, 2000;Gurganus, 2007).…”
Section: Receptive Language Challengesmentioning
confidence: 99%